ANALYSIS OF WHEAT FLOUR DEMAND IN MEDAN CITY - Ummul Hikmah Saragih; Dian Hafizah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study analyzes the demand for wheat flour in Medan City, with the aim of determining the effect of wheat flour prices and income on demand. Using the Marshallian Linear Demand model, the data used covers the period 2018-2023. The results of the analysis show that wheat flour prices have a significant effect on demand, with a coefficient of 0.165, while the effect of income is not significant with a coefficient of 0.016. The regression model used shows an R-squared value of 0.842, indicating that this model is able to explain 84.2% of the variation in wheat flour demand. The classical assumption test shows that there are no problems of multicollinearity, heteroscedasticity, and autocorrelation, and the data is normally distributed. These findings provide insight into the dynamics of wheat flour demand and its implications for marketing strategies in the agricultural sector.